Effect of post shelling storage environments on seed germination and vigor of peanut. (3rd September 2021) - Weaver, Caleb C.; Monfort, W. Scott; Grey, Timothy L.; Pilon, Cristiane; Tubbs, R. Scott
Abstract: Proper storage of peanut( Arachis hypogaea L.) seed is essential for maintaining viability to ensure adequate plant stands are achieved upon planting. Experiments conducted in Georgia from 2017 to 2018 evaluated cultivar by storage condition by sampling date effects on three peanut cultivars. The effects of varying environments, with respect to different temperatures and humidity, on peanut seed viability was evaluated when stored up to 72 d. Seed germination and vigor were assessed in petri dishes on a thermal gradient table with temperatures ranging from 10.2 to 33.2 °C and incubated for 7 d. Daily mean temperature data were used to calculate growing degree day (GDD) accumulation via thermocouples. Maximum germination rates ( b 0 ) and GDD values at 80% germination (Germ80) were quantified. Results indicated that germination and vigor varied by cultivar, storage environment, and sampling date with respect to GDDs required to reach Germ80 and maximum germination (b0). Storage environment treatments consisted of (a) 9–12 °C and 43–51% relative humidity (RH), (b) 18–27 °C and 42–54% RH, (c) 12–37 °C and 48–74% RH, and (d) 24–46 °C and 33–85% RH. Storage environments affected seed germination, where environments with large fluctuations in temperature and RH (12–37 °C, 48–74% RH and 24–46 °C, 33–85% RH) for up to 72 d resulted in decreased percentage germination (>20 points) and vigor (>5 GDDs). However, excellent seed germinationand vigor were sustained where storage temperatures were below 18 °C and RH was below 54%. Therefore, maintaining proper temperatures and RH is key to sustaining seed quality (germination and vigor) over time. Core Ideas: Seed is one of the highest input costs in peanut production. Storage conditions with extreme diurnal fluctuations cause a significant decline in seed germination. Maintaining suitable temperatures and relative humidity within storages are extremely important to sustaining seed viability. Increasing awareness of storage condition effects on seed can promote better stands.